HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN KOORDINASI MATA DAN TANGAN TERHADAP KEMAMPUAN PUKULAN FOREHAND PADA ATLET PUTRA KLUB PERSATUAN TENIS MEJA MANDIRI - Taufik Samur; Ramadi Ramadi; Zainur Zainur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on the observations of researchers in the field at the location of the table tennis club Mandiri in the district. Siak Hulu Kab. Kampar, researchers saw a lack of male athletes from the table tennis club Mandiri making a forehand. Where athletes hit the ball that is hit when making a forehand, it often goes out or does not enter the opponent's field. The aim of this study was to determine the relationship between wrist flexion and eye and hand coordination with manual dexterity in male athletes at the Independent Table Tennis Club. The population in this study consisted of 8 male table tennis association Mandiri athletes. The sampling technique in this study is the total sampling technique. This means that the entire population is sampled, so the sample in this study was 8 people. The results of this study have been analyzed with correlation. Based on the analysis of the correlation between wrist flexibility and forehand results r count 0.620 obtained while the r table at a significant level is α = 0.05 0.754. in this case means that there is a relationship between wrist flexibility and the result of a forehand. From the results of the calculation of the correlation between eye and hand coordination with the r count 0.817 obtained in advance, while the r table at a significant level is α = 0.05 0.754. In this case, means that there is a link between eye and hand coordination with the ability to forhand. From the calculation results obtained by the multiple correlation coefficient (R test) R count = 0.856, while the R table was obtained with 0.754, so R count> R table, meaning there is a joint relationship between wrist flexion (X1 ) and eye and hand coordination (X2) with the skill in advance (Y). Key Words: Wrist Speculation, Eye and Hand Coordination, Forehand Punch Ability